Synthesis of tinidazole by condensation-oxidation sequence using MoO3/SiO2 bifunctional catalyst - Chandorkar, J. G.; Shubhangi B. Umbarkar; Rode, C. V.; Kotwal, V. B.; Dongare, Mohan K. (Catalysis Communications, 2007)
Antimicrobial drug, tinidazole has been synthesized by condensation of 2-methyl,5-nitro-imidazole and 2-ethyl-thio-ethanol over MoO3/SiO2 catalyst to obtain 1-(2-ethyl-thio-ethanol)-2-methyl-5-nitro-imidazole which is further oxidized using hydrogen peroxide using the same MoO3/SiO2 catalyst to obtain tinidazole. MoO3/SiO2 catalyst (20%), synthesized by sol-gel process showed the highest acid strength and was successfully demonstrated to catalyze both condensation and oxidation in the synthesis of tinidazole. Due to the bifunctional activity of the catalyst, the use of acetic acid for condensation step and tungstic acid or ammonium molybdate for oxidation step in the conventional synthesis of tinidazole could be eliminated, thus making it an environmentally benign process. The catalysts could be recycled five times without any appreciable loss in the conversion and selectivity showing the potential for. the use of MoO3/SiO2 as bifunctional catalyst for the production of this industrially important compound. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: antimicrobial drug; condensation; MoO3/SiO2; Oxidation; solid acid catalyst; tinidazole

Selective cis-dihydroxylation of olefins using recyclable homogeneous molybdenum acetylide catalyst - Biradar, Ankush V.; Sathe, Bhaskar R.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Journal of Molecular Catalysis A-Chemical, 2008)
Selective cis-dihydroxylation of various olefins has been carried out using molybdenum acetylide complex CpMO(CO)(3)(C CPh) (1) as catalyst and hydrogen peroxide as an efficient and environmentally benign oxidant. In case of cyclohexene, very high conversion (95%) and selectivity (86%) for cis-dihydroxylated product has been achieved using H2O2 as an oxidant and t-butanol as a solvent. cis-Dihydroxylation of other substrates like styrene, a-methyl styrene, limonene and cyclopentene has also been carried out with very high selectivity for diol. The catalyst and intermediate species have been characterized using FT-IR, UV-vis spectral analysis and XPS studies as well as cyclic voltametric studies. These studies suggest that molybdenum oxo-peroxo complex is the catalytically active species. The intermediate blue complex when characterized by ESI MS suggested the formation of dimeric molybdenum complex and XPS and cyclic voltametric studies confirm the presence of mixed valence Mo(V) and Mo(VI) in the reaction intermediate. Based on the characterization results possible mechanism for dihydroxylation is proposed. Interestingly, even though the catalyst is homogeneous; it could be recovered quantitatively by extraction in aqueous phase and recycled five times without any appreciable loss in cyclohexene conversion and selectivity for cis-1,2-cyclohexanediol. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: acetylide complex; cis-dihydroxylation; Homogeneous catalysis; Hydrogen peroxide; recyclable

Selective N-oxidation of aromatic amines to nitroso derivatives using a molybdenum acetylide oxo-peroxo complex as catalyst - Biradar, Ankush V.; Kotbagi, Trupti V.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Tetrahedron Letters, 2008)
The molybdenum acetylide oxo-peroxo complex obtained in situ by the treatment of the corresponding molybdenum acetylide carbonyl complex, CpMo(CO)(3)(C CPh); Cp = eta(5-)C(5)H(5) with H(2)O(2), has been used as an efficient catalyst for selective N-oxidation of primary amines to nitroso derivatives. Excellent amine conversion (up to 100%) and very high selectivity for nitroso compounds (99%) have been obtained using 30% hydrogen peroxide as an oxidant. The oxo peroxo, Mo(VI) complex has also been found to be very active for the oxidation of various substituted primary aromatic amines with electron donating as well as electron withdrawing substituents on the aromatic ring. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: aromatic amine; Homogenous catalyst; Hydrogen peroxide; Molybdenum complex; nitroso; Oxidation; Oxo-peroxo

Selective oxidation of aromatic primary alcohols to aldehydes using molybdenum acetylide oxo-peroxo complex as catalyst - Biradar, Ankush V.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Tetrahedron Letters, 2009)
Selective oxidation of various aromatic alcohols to aldehydes has been carried out with very high conversion (90%) and selectivity (90%) for aldehydes using cyclopentadienyl molybdenum acetylide complex, CpMo(CO)(3)(C CPh) (1) as catalyst and hydrogen peroxide as environmentally benign oxidant, Water-soluble Mo acetylide oxo-peroxo species is formed in situ after reaction of I with aqueous hydrogen peroxide during the Course of reaction as catalytically active species. Interestingly even though the catalyst is homogeneous it Could be recycled very easily by separating the products in organic phase and catalyst in aqueous phase using separating funnel. Even after five recycles no appreciable loss in alcohol conversion and aldehyde selectivity was observed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Homogenous catalyst; Hydrogen peroxide; Molybdenum complex; Oxidation; Oxo-peroxo; Primary aromatic alcohol

Support modification to improve the sulphur tolerance of Ag/Al2O3 for SCR of NOx with propene under lean-burn conditions - Jagtap, Neelam; Shubhangi B. Umbarkar; Miquel, Pierre; Granger, Pascal; Dongare, Mohan K. (Applied Catalysis B-Environmental, 2009)
Ag/Al2O3 catalysts with 1 wt% SiO2 or TiO2 doping in alumina support have been prepared by wet impregnation method and tested for sulphur tolerance during the selective catalytic reduction (SCR) of NOx using propene under lean conditions, Ag/Al2O3 showed 44% NOx conversion at 623 K, which was drastically reduced to 21% when exposed to 20 ppm SO2. When Al2O3 support in Ag/Al2O3 Was doped with 1 wt% SiO2 or TiO2 the NOx conversion remained constant in presence of SO2 showing the improved sulphur tolerance of these catalysts. Subsequent water addition does not induce significant deactivation. On the contrary, a slight promotional effect on the activity of NO conversion to nitrogen is observed after Si and Ti incorporation. FTIR study showed the sulphation of silver and aluminum sites of Ag/Al2O3 catalysts resulting in the decrease in the formation of reactive intermediate species such as -NCO, which in turn decreases NOx conversion to N-2. In the case of Ag/Al2O3 doped with SiO2 or TiO2, formation of silver sulphate and aluminum sulphate was drastically reduced, which was evident in FTIR resulting in remarkable improvement in the sulphur tolerance of Ag/Al2O3 catalyst. These catalysts before and after the reaction have been characterized with various techniques (XRD, BET surface area, transmittance FTIR and pyridine adsorption) for physico-chemical properties. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ag/Al2O3; Aluminum sulphate; DRIFTS; Selective catalytic reduction; Silver sulphate; SiO2; Sulphur tolerance; TiO2

Synthesis of catalytically active porous platinum nanoparticles by transmetallation reaction and proposition of the mechanism - Pasricha, Renu; Bala, Tanushree; Biradar, Ankush V.; Shubhangi B. Umbarkar; Sastry, Murali (Small, 2009)
A facile method for the synthesis of porous platinum nanoparticles by transmetallation reactions between sacrificial nickel nanoparticles and chloroplatinic acid (H(2)PtCl(6)) in solution, as well as at the constrained environment of the air water interface, using a Langmuir-Blodgett instrumental setup is presented. To carry out the transmetallation at the air-water interface hydrophobized nickel nanoparticles are assembled as a monolayer on the sub phase containing platinum ions. The porous Pt nanoparticles obtained as a result of the reaction are found to act as extremely good catalysts for hydrogenation reaction. The products are well characterized by TEM, HRTEM, EDAX, and STEM. Attempts are made to postulate the plausible mechanism of this reaction to generate this kind of nanoparticle with controllable geometric shape and structure. This simple strategy has the potential to synthesize other nanomaterials of interest too.
Keywords: Catalysts; Interfaces; Nickel nanoparticles; porous platinum; Transmetallation

Selective oxidation of nonrefractory and refractory sulfides by cyclopentadienyl molybdenum acetylide complexes as efficient catalysts - Chandgude, Macchindra G.; Biradar, Ankush V.; Kotbagi, Trupti V.; Puranik, Vedavati G.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Catalysis Letters, 2012)
{The synthesis and catalytic properties of molybdenum acetylide complexes CpMo(CO)(3)(-C CR)
Keywords: Homogeneous catalysis; Molybdenum acetylide; Oxo-peroxo species; Refractory sulfide oxidation

Silica microspheres containing high density surface hydroxyl groups as efficient epoxidation catalysts - Chandra, Prakash; Doke, Dhananjay S.; Shubhangi B. Umbarkar; Vanka, Kumar; Biradar, Ankush V. (RSC Advances, 2015)
Uniformly sized silica microspheres were synthesized by a hydrolysis-condensation method. The obtained material was etched with a mild aqueous potassium hydroxide solution for different periods of time to break their Si-O-Si bonds and increases the density of hydroxyl groups on their surfaces. The resulting materials were then used as transition metal-free catalysts for oxidation of olefins in the presence of hydrogen peroxide as a green oxidant. The materials were thoroughly characterized using various physicochemical techniques. These highly populated hydroxyl groups on the surface of silica microspheres were proven to be responsible for excellent conversion (up to 93%) and epoxide selectivity (up to 100%) for various olefins. Quantum mechanical calculations also corroborate the experimental findings. Furthermore, both experimental and theoretical studies show that tertiary silanols were present at the active sites of the catalyst surface and were responsible for olefin epoxidation.

Sol-gel synthesised WO3 nanoparticles supported on mesoporous silica for liquid phase nitration of aromatics - Kulal, A. B.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2016)
A series of WO3/SiO2 catalysts have been prepared by sol-gel method using ammonium metatungstate and ethyl silicate-40 (ES-40) as WO3 and SiO2 precursors respectively. The sol-gel method has led to the formation of WO3 nano-particles of 2-5 nm well dispersed on mesoporous silica along with some WO3' agglomerates. Formation of monoclinic WO3 was seen on the catalysts above 5 wt% WO3 loading by XRD analysis. Silica has shown very high surface area of 606 m(2)/g which decreased gradually upto 368 m(2)/g with 20 wt% WO3 loading. 20 wt% WO3/SiO2 catalyst has shown maximum acidity (0.56 mmol NH3/g) with presence of both Lewis and Bronsted acidity. UV-vis DRS analysis showed formation of polytungstate species along with WO3 on silica surface. The prepared catalysts were used for liquid phase nitration of aromatics using 70% nitric acid as nitrating agent without using any sulfuric acid. Very high conversion (99%) was obtained for p-cresol nitration with very high selectivity (99%) for 2-nitro p-cresol. The water formed during the reaction was removed azeotropically using ethylene dichloride as solvent. In case of o-xylene 74% conversion was obtained with 54% selectivity for 4-nitro o-xylene. The effect of different WO3 precursors on nitration efficiency was studied using sodium tungstate and tungstic acid as precursors. However,ammonium metatungstate showed the highest acidity. Sodium tungstate showed formation of dimer of sodium tungstate which did not show any acidity and hence no activity for nitration. The mechanism for nitration using WO3/SiO2 has been proposed based on polarisation of water on tungsten centre generating Bronsted acidity which can further generate nitronium ion giving subsequently nitration of the aromatic ring. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aromatic nitration; heterogeneous catalysis; Regioselective; Sol-gel synthesis; Water polarization